Green Synthesis of Gold Nanoparticles from E-Waste for Colorimetric Detection of Salmonella sp - Ansyarif, Azmalaeni Rifkah; Nur Aeni; Sri Magfirah HS (Al-Kimia, 2025)
The rapid increase in electronic waste (e-waste) presents environmental and health risks, while also serving as a secondary source of valuable metals such as gold. This study recovered gold from e-waste and synthesized gold nanoparticles (AuNPs) via a green synthesis approach using ascorbic acid as a natural reducing agent, followed by evaluation of their potential as a colorimetric sensor for Salmonella sp. detection. Gold was extracted through pyrolysis and leaching to obtain HAuCl₄ precursor solution, which was subsequently reduced by ascorbic acid to form AuNPs. Characterization by TEM, PSA, and UV–Vis confirmed successful synthesis: TEM showed predominantly spherical particles of 20–50 nm, PSA indicated an average size of 82.6 nm, and UV–Vis revealed a distinct Surface Plasmon Resonance (SPR) peak at 520–560 nm. Colorimetric assays demonstrated a linear absorbance response to Salmonella sp. concentration, achieving a detection limit (LOD) of 13.33 CFU/mL. These results demonstrate that gold recovered from e-waste can be converted into functional AuNPs through environmentally friendly synthesis with ascorbic acid, providing a promising platform for rapid and sensitive biosensing applications in food safety.